Steps and Factors of Process of the Effective Management Decision in Higher Educational Institutions - Shakirova Charos Turgunovna; Toshtonov Soyibjon Abdusami o`g`li (International Journal on Integrated Education, 2021)
This article emphasizes that the effectiveness of effective management decisions in higher education institutions depends on several stages and factors, it is very important to compare the result achieved in management decision making with the expected result before making it. The article explains that this is the basis for effective decision-making.